2021
DOI: 10.1101/2021.09.15.21262513
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Peripheral Arteriovenous Malformations and Their Response to Treatment Modalities: A Single Surgeon’s Experience at Tertiary Care Hospitals

Abstract: Background Peripheral arteriovenous malformations (AVMs) are congenital defects resulting in abnormal connections between veins and arteries. We investigated a group of patients with peripheral AVMs to determine whether there were any gender differences in disease presentation and the response of AVMs to various modalities of treatment. Methodology The patients in this cross-sectional study were divided into two groups based on gender and their demographic data, clinical presentation at the time of diagnosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The proliferating phase of infantile hemangiomas in its proliferation phase is also a high-flow lesion which is categorized as a vascular tumor rather than malformation which shows regression with time, unlike vascular malformations (Malik et al 2021) [17]. Similar results was also published by Usman, Rashid, et al [14] and Nosher J [18]. The "Little AVMs", as defined by Stein et al [19] are malformations on the spectrum between AVMs and venous malformations.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The proliferating phase of infantile hemangiomas in its proliferation phase is also a high-flow lesion which is categorized as a vascular tumor rather than malformation which shows regression with time, unlike vascular malformations (Malik et al 2021) [17]. Similar results was also published by Usman, Rashid, et al [14] and Nosher J [18]. The "Little AVMs", as defined by Stein et al [19] are malformations on the spectrum between AVMs and venous malformations.…”
Section: Discussionsupporting
confidence: 52%
“…The male to female incidence of AVMs in our study was 1: 1.3 which is in concordance with the study of Lee BB et al who also reported male: female ratio of 1: 1 to 1: 2 [9], whereas Usman, Rashid, et al reported a slightly higher male to female ratio of 1:3. Furthermore, the average age at presentation in female patients was younger compared to male patients [14]. Two factors might account for these findings.…”
Section: Discussionmentioning
confidence: 90%